Reduced Graphene Oxide Prepared by Hydrothermal Method as Microwave Absorber Filler - BINTI HASHIM, NURUL HALIZA; ESA, FAHMIRUDDIN BIN (Enhanced Knowledge in Sciences and Technology, 2022)
Reduced graphene oxide (RGO) has excellent electrical conductivity due to hybridized energy bonding other than higher specific surface area. Most of the case, the preparation involved the use of hazardous reducing agents. However, recent studies show that water can be used as the replacing agent and make the method, namely hydrothermal provides a new and “green” technique. In this work, RGO was synthesized at different pH values; 4, 7 and 11. Morphological structure shows that the RGO like a sheet shape and get stacked with each other and it seems less stack for pH 11. The fingerprint of the RGO was done by functional group observation. The lateral dimensions of graphene sheet were estimated by dynamic light scattering (DLS) technique, which indicates lower in size, 355.5 nm for higher pH value. Permittivity value of 4%-RGO/epoxy composite however almost similar about 8 and stable at 5 GHz and above. The composite was later designed as planar absorber and simulated at various thickness via free space technique. Major absorption is found at the bandwidth of 1.88 GHz for 10 mm thickness. The most minimum return loss (RL) is -22 dB at 7.34 GHz, suggesting that the thickness is comparable with quarter lambda of the resonance frequency. Therefore, the composite is suitable to be used as microwave absorber at the respective loading percentage of filler, thickness and frequency range.